2018
DOI: 10.1080/21691401.2018.1500372
|View full text |Cite
|
Sign up to set email alerts
|

Modified PAMAM vehicles for effective TRAIL gene delivery to colon adenocarcinoma:in vitroandin vivoevaluation

Abstract: TRAIL (tumour necrosis factor-related apoptosis-inducing ligand) gene therapy is considered as one of the promising approaches for cancer treatment. Polyamidoamine (PAMAM) is one of the most extensively applied polymeric vector in gene delivery. In the current study, PAMAM (G4 and G5) dendrimers were modified with alkyl-carboxylate chain, PEG and cholesteryl chloroformate in order to enhance transfection efficiency through overcoming extracellular and intracellular barriers while reducing PAMAM cytotoxicity. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…It is also reported that Wnt signaling in tumor cells is inhibited by chemerin while nexin is a downstream target of Wnt signaling [43][44][45]. We also observed that the levels of p53 and TRAIL were elevated by dopamine and reduced by cholesterol, in which p53 is a well-known tumor suppressor [46], and TRAIL is an apoptosis inducer of tumor cells [47]. Taken together, this study indicates that the upregulation of chemerin, TRAIL, and p53 as well as the downregulation of nexin by mechanical loading contributes to Lrp5-dependent and independent mechanisms by downregulating Lrp5, MMP2, MMP3, MMP9, Runx2, Snail, and TGFβ in tumor cells.…”
Section: Discussionsupporting
confidence: 65%
“…It is also reported that Wnt signaling in tumor cells is inhibited by chemerin while nexin is a downstream target of Wnt signaling [43][44][45]. We also observed that the levels of p53 and TRAIL were elevated by dopamine and reduced by cholesterol, in which p53 is a well-known tumor suppressor [46], and TRAIL is an apoptosis inducer of tumor cells [47]. Taken together, this study indicates that the upregulation of chemerin, TRAIL, and p53 as well as the downregulation of nexin by mechanical loading contributes to Lrp5-dependent and independent mechanisms by downregulating Lrp5, MMP2, MMP3, MMP9, Runx2, Snail, and TGFβ in tumor cells.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, in vivo studies demonstrated that G5-DAT66/pTRAIL efficiently inhibited tumor growth in osteosarcoma-bearing mice. Pishavar et al synthesized a vector composed of PAMAM dendrimers modified with alkyl-carboxylate chains, PEG, and cholesteryl chloroformate for delivering pTRAIL, and these PAMAM G4-alkyl-PEG (3%)-Chol (5%)-TRAIL complexes inhibited CT26 tumor growth in mice [67].…”
Section: Nonviral Vectorsmentioning
confidence: 99%
“…Genetic mutations in specific genes increase the risk of developing the disease [25]. Gene delivery systems have been widely applied to develop gene therapy classified to viral and nonviral vectors [26]. Local delivery to the retina can increase half-life therapeutic agents and reduce immune reactions, while direct retinal gene/drug delivery is a remarkably invasive procedure [27].…”
Section: Novel Drug Delivery Systemsmentioning
confidence: 99%